2014
DOI: 10.1021/jp5093288
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Intramolecular Charge Transfer State Formation in all-trans-β-Apo-8′-carotenal: Influence of Solvent Polarity and Polarizability

Abstract: In this work we analyzed the infrared and visible transient absorption spectra of all-trans-β-apo-8'-carotenal in several solvents, differing in both polarity and polarizability at different excitation wavelengths. We correlate the solvent dependence of the kinetics and the band shape changes in the infrared with that of the excited state absorption bands in the visible, and we show that the information obtained in the two spectral regions is complementary. All the collected time-resolved data can be interpret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
38
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 63 publications
10
38
2
Order By: Relevance
“…As already noticed, the character of the ICT state strongly depends on the ambient polarity; to get a better insight of its formation dynamics and evolution, we repeated the measurements in two solvents: the non-polar cyclohexane and the slightly polar chloroform. 27 Representative transient spectra at different pump-probe delays for all the excitation wavelengths are reported in Figure 3.…”
Section: B Transient Infrared Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…As already noticed, the character of the ICT state strongly depends on the ambient polarity; to get a better insight of its formation dynamics and evolution, we repeated the measurements in two solvents: the non-polar cyclohexane and the slightly polar chloroform. 27 Representative transient spectra at different pump-probe delays for all the excitation wavelengths are reported in Figure 3.…”
Section: B Transient Infrared Measurementsmentioning
confidence: 99%
“…18,25 These studies revealed that the formation of the ICT state is related to the chain length and is enhanced in short chain analogues; in addition, the amount of polyene conjugation also regulates the energy difference between S 2 and S 1 states. In recent papers, 26,27 we analyzed the deactivation pathway of a different and structurally simpler carbonyl carotenoid, trans-β-apo-8 ′ -carotenal, by means of visible pump/Mid-IR probe spectroscopy, transient absorption spectroscopy, and transient 2DIR spectroscopy. Initial data were recorded in two solvents with different polarities, the nonpolar cyclohexane and the slightly polar chloroform, and the measurements were subsequently extended to a number of solvents, differing both in polarity and polarizability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For ω VIS < 19200 cm −1 , a broad negative transient dominates, attributed to S n ← S 1 excited state absorptions (ESAs). Our degenerate electronic pump−probe experiments offer a superior instrument response (27 fs) than previous TA studies of β-apo-8′-carotenal; 16,33 however, they do not stretch below ω VIS = 18200 cm −1 , where in polar solutions the ESAs from the ICT state are expected to peak at ∼15400 cm −1 (∼650 nm). 11,14,16 The broadband degenerate TA data could not be analyzed in a self-consistent manner by fitting the decay of individual probe frequencies− the ground state absorption stretches almost the entire probe window, and overlaps with the very broad S n ← S 1 ESAs.…”
Section: Resultsmentioning
confidence: 85%
“…The specific lifetimes for the different decay components are given in Table 1 and are in agreement with previous literature values of the S 2 and S 1 lifetimes. 29,32,33 c. Electronic-Vibrational Spectroscopy. i. Cyclohexane.…”
Section: Resultsmentioning
confidence: 99%